Concomitant administration of diphtheria, tetanus, acellular pertussis and inactivated poliovirus vaccine derived from Sabin strains (DTaP-sIPV) with pentavalent rotavirus vaccine in Japanese infants - Yoshiyuki Tanaka; Ruriko Yokokawa; Han Shi Rong; Hiroyuki Kishino; Jon E. Stek; Margaret Nelson; Jody Lawrence (Taylor & Francis Group, 2017)
Rotavirus is the leading cause of severe acute gastroenteritis in infants and young children. Most children are infected with rotavirus, and the health and economic burdens of rotavirus gastroenteritis on healthcare systems and families are considerable. In 2012 pentavalent rotavirus vaccine (RV5) and diphtheria, tetanus, acellular pertussis and inactivated poliovirus vaccine derived from Sabin strains (DTaP-sIPV) were licensed in Japan. We examined the immunogenicity and safety of DTaP-sIPV when administrated concomitantly with RV5 in Japanese infants. A total of 192 infants 6 to 11 weeks of age randomized to Group 1 (N = 96) received DTaP-sIPV and RV5 concomitantly, and Group 2 (N = 96) received DTaP-sIPV and RV5 separately. Antibody titer to diphtheria toxin, pertussis antigens (PT and FHA), tetanus toxin, and poliovirus type 1, 2, and 3 were measured at 4 to 6 weeks following 3-doses of DTaP-sIPV. Seroprotection rates for all components of DTaP-sIPV were 100% in both groups, and the geometric mean titers for DTaP-sIPV in Group 1 were comparable to Group 2. Incidence of systemic AEs (including diarrhea, vomiting, fever, and nasopharyngitis) were lower in Group 1 than in Group 2. All vaccine-related AEs were mild or moderate in intensity. There were no vaccine-related serious AEs, no deaths, and no cases of intussusception during the study. Concomitant administration of DTaP-sIPV and RV5 induced satisfactory immune responses to DTaP-sIPV and acceptable safety profile. The administration of DTaP-sIPV given concomitantly with RV5 is expected to facilitate compliance with the vaccination schedule and improve vaccine coverage in Japanese infants.